2007
DOI: 10.1007/s10608-006-9090-1
|View full text |Cite
|
Sign up to set email alerts
|

Do Religious and Control Cognitions Predict Risky Behavior? II. Development and Validation of the Sexual Risk Behavior-related God Locus of Control Scale for Adolescents (SexGLOC-A)

Abstract: Research has identified numerous correlates of sexual risk behaviors among adolescents. However, two potentially important cognitive constructs, perceived control and religious beliefs, have received considerably less attention. Research demonstrates that the most informative examination of the relationship of perceived control beliefs to sexual risk requires instruments that directly assess control beliefs specific to sexual risk behaviors. Further, beliefs about God as a source of control (e.g., the percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
2
11
1
Order By: Relevance
“…Consistent with other work with adolescents (Goggin et al, 2007), AGLOC-A scores were, in general, independent of internal control beliefs. This finding supports the contention that God control beliefs are not merely the opposite of internal control beliefs, but rather are orthogonal to these beliefs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with other work with adolescents (Goggin et al, 2007), AGLOC-A scores were, in general, independent of internal control beliefs. This finding supports the contention that God control beliefs are not merely the opposite of internal control beliefs, but rather are orthogonal to these beliefs.…”
Section: Discussionsupporting
confidence: 87%
“…These findings provide evidence of concurrent criterion validity and suggest that alcohol-specific God control beliefs are predictive of drinking behavior in African American adolescents. These results are also consistent with our experience in developing a similar measure focused on adolescent sexual risk behavior (Goggin, Malcarne, Murray, Metcalf, & Wallston, 2007) and, while not conclusive, suggests the possibility that youth who believe that God is actively helping them to make adaptive decisions may be empowered to resist engagement in risky behaviors.…”
Section: Discussionsupporting
confidence: 79%
“…Other investigators reported that a greater sense of God control is associated with the greater use of beneficial coping responses (Welton, Adkins, Ingle, & Dixon, 1996). Goggin et al (2007) examined whether God control beliefs influence health behaviors. More specifically, these investigators found that stronger God control beliefs are associated with a lower probability of engaging in risky sex practices (e.g., having fewer sexual partners).…”
mentioning
confidence: 99%
“…This is not surprising, since 85 % reported that they prayed regularly. A study by Goggin et al (2007) found that African American youth tended to perceive God as loving and offering support in making decisions about sexual behavior, and perceiving God as being actively involved in youths' decision-making processes was associated with stronger intentions to delay sex and less sexual risk behavior. These findings suggest the need for further research on how aspects of the youth-God relationship can be effectively incorporated in parent-child-church sex communication and how a supportive sex education church environment can jointly protect against sexual risk behaviors.…”
Section: Discussionmentioning
confidence: 99%